Developing Strategies for Integrating Indigenous Health and Modern Health Systems for Improved Adolescent Sexual Health Outcomes in Umguza and Mberengwa Districts in Zimbabwe - Wilfred Njabulo Nunu; Lufuno Makhado; Jabu Tsakani Mabunda; Rachel Tsakani Lebese (SAGE Publishing, 2021)
Background: Strategies to improve sexual health outcomes have evolved over the years due to technology's evolution to ensure that they are relevant. Challenges have been noticed in different systems that run parallel, particularly in Low-Income Countries where the majority utilise Indigenous Health Systems. Optimisation of resources and minimisation of conflicts could be realised through integrated health systems in the management of adolescents' sexual health issues. This study sought to develop strategies to facilitate Indigenous Health System and Modern Health System integration to improve the management of Adolescent Sexual Health issues, leveraging results from 3 papers. Methods: A multi-stage approach was utilised, with Phase 1 focussing on a preliminary assessment through merging findings from the 4 papers. The Strengths, Weaknesses, Opportunities, and Threats analyses were then used, followed by the Basic Logic Model to identify critical aspects that needed to be considered in building the strategies. The second phase used the Build, Overcome, Eliminate and Minimise framework to build the strategies. Results: A total of 5 strategies were proposed to facilitate this integration, and these included revival of committees that were inclusive of all stakeholders; allocating Indigenous Health System space in clinics to work in; establishing adolescent-friendly clinics; intensifying information dissemination on sexual health-related issues, and developing clear Terms of Reference and procedures to govern this integration and ensure it is a success. Conclusions: Implementing these strategies could facilitate this integration and ensure that programs are planned and implemented in a complementary manner, thereby reducing conflicts between the 2 systems and ensuring collaborative efforts towards shared goals that would transform to better Sexual Health Outcomes for adolescents.